Construction of Binary Vector and Transformation of Synthetic LcCsp Gene into Nipponbare Rice Genome by Agrobacterium tumefaciens Transformation Method - Dina Sri Yulita; Aqwin Polosoro; Atmitri Sisharmini; Aniversari Apriana; Febi Nurilmala; Kurniawan Rudi Trijatmiko (Jurnal AgroBiogen, 2020)
Cold shock protein (Csp) is an essential bacterial protein for increasing abiotic stress tolerance, especially cold stress. Several studies discovered that overexpression of the gene successfully improves the tolerances of several types of plant not only under cold stress, but also other abiotic stresses, e.g. hot and drought conditions. The objectives of this study were to construct a binary vector containing the LcCsp gene modified from Lactobacillus casei and transform the gene into Nipponbare rice genome. The native LcCsp gene sequence, however, has low GC content (46.7%) while rice as transformation target plant has 52% GC content. The native LcCsp gene sequence, therefore, was optimized to the level close to 52.7% similar to GC content of the rice genome. This LcCsp gene was synthesized by using DNA printing technology (gBlocks® Gene Fragments Entry, IDT). The synthetic LcCsp gene was successfully inserted into the pCAMBIA1300-int binary vector driven by Ubiquitin1 promoter and NOS terminator. The T-DNA cassette was successfully transformed into Nipponbare rice genome by Agrobacterium tumefaciens strain LBA4404 using immature embryo transformation protocol. A total of 51 T0 Nipponbare lines survived from hygromycin selections and 21 lines were successfully acclimatized. Molecular analysis of the candidate lines showed that all Nipponbare transgenic putative lines contain the LcCsp gene demonstrating high transformation efficiency of 11.8%. The rice lines resulted from this study should be further analyzed and might be useful for developing rice transgenic lines tolerance to heat, drought, or saline stress condition.